EFFECTIVENESS OF CASSIA AURICULATA FLOWER (AVARAM POO) EXTRACT IN REDUCING BLOOD GLUCOSE AMONG PRE DIAGNOSED TYPE 2 DIABETES MELLITUS CLIENTS IN SELECTED AREA OF PUDUCHERRY, INDIA - Sankhari, J (LIFE: International Journal of Health and Life-Sciences, 2019)
A study to evaluate the effectiveness of Cassia auriculata (Avaram poo) Flower extract in reducing blood glucose among pre diagnosed Type 2 Diabetes Mellitus clients in selected area of Puducherry. Objectives of the study are to assess the pretest level blood glucose among the control and experimental group. To administer the Cassia auriculata (Avaram poo) flower extract to the study group, To assess the post test level blood glucose among the control and experimental group, To evaluate the effectiveness of Cassia auriculata Flower (Avaram poo) extract in reduction of blood glucose level among type2 Diabetes Mellitus subjects, To associate the effectiveness of Cassia auricular Flower (Avaram poo) extract with demographic variables in experimental group. The research approach selected for the study was Quantitative approach, quasi Experimental design (pre-test and post test with control group). The study was conducted in selected PHC Kalapet, at Puducherry. Sample size was 60, 30 in experimental and 30 in control group were randomly assigned. The standardized glucometer was used to assess the blood glucose level. Pretest was done to assess the level blood glucose (FBS and PPBS) for both the groups. Experimental group received Cassia auriculata Flower (Avaram poo) extract for 30 days and control group did not receive any measures. Post test level of blood Glucose (FBS and PPBS) was evaluated on 30th day for both experimental and control group. The results of the study were the result revealed that the pretest mean score of fasting blood glucose was 133.50±37.43 and after the administrations of Cassia auriculata flower extract the post test mean score was 109.93±18.14. The mean difference score was 23.57. The calculated paired‘t’ value of t =5.478 was found to statistically highly significant at p<0.,001 level. This clearly indicates that the Cassia auriculata flower extract was found to be effective in reducing the fasting blood glucose level among type 2 diabetes mellitus clients in the experimental group. The pretest mean score of post prandial blood glucose was 262.40±73.18 and after the administrations of Cassia auriculata flower extract the post test mean score was 193.43±45.99. The mean difference score was 68.97. The calculated paired ‘t’ value of t = 8.103 was found to statistically highly significant at p<0.001 level. This clearly indicates that the Cassia auriculata flower extract was found to be effective in reducing the post prandial blood glucose level among pre diagnosed type 2 diabetes mellitus clients in the experimental group. The demographic variable of marriage had shown significant association with the post test level of fasting blood glucose among the study group.